2011
DOI: 10.1134/s1063778811070131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Z′-mediated flavor-changing neutral current on B → ππ decays

Abstract: We study the effect of Z ′ -mediated flavor-changing neutral current on the π π → B decays. The branching ratios of these decays can be enhanced remarkably in the nonuniversal Z ′ model. Our estimated branching ratios

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Various studies of the nonuniversal model have been done assuming diagonal as well as vanishing right-handed quark couplings with boson. It is observed that it can help to resolve the puzzles of rare B meson decays such as ̅ mixing phase [51], puzzle [50,52], puzzle [53,54], etc.…”
Section: The Non-universal Modelmentioning
confidence: 99%
“…Various studies of the nonuniversal model have been done assuming diagonal as well as vanishing right-handed quark couplings with boson. It is observed that it can help to resolve the puzzles of rare B meson decays such as ̅ mixing phase [51], puzzle [50,52], puzzle [53,54], etc.…”
Section: The Non-universal Modelmentioning
confidence: 99%
“…In the Z ′ sector, there has been a great deal of investigation to understand the underlying physics beyond the SM [37][38][39][40][41][42][43]. It has been shown that a leptophobic Z ′ boson can appear in 6 E gauge models due to mixing of gauge kinetic terms [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%